2011
DOI: 10.1038/nn.2933
|View full text |Cite
|
Sign up to set email alerts
|

Dorsolateral and ventromedial prefrontal cortex orchestrate normative choice

Abstract: Humans are noted for their capacity to over-ride self-interest in favor of normatively valued goals. We examined the neural circuitry that is causally involved in normative, fairness-related decisions by generating a temporarily diminished capacity for costly normative behavior, a 'deviant' case, through non-invasive brain stimulation (repetitive transcranial magnetic stimulation) and compared normal subjects' functional magnetic resonance imaging signals with those of the deviant subjects. When fairness and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
222
2
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(253 citation statements)
references
References 49 publications
25
222
2
4
Order By: Relevance
“…Similar stimulation parameters (i.e., fixed intensity of stimulation, 15 minutes of stimulation) have been used before to suppress activity of prefrontal regions prior to task requiring social judgments (e.g., reciprocal fairness, moral judgments), with the effects of stimulation continuing after the end of the actual stimulation (e.g., Baumgartner, Knoch, Hotz, Eisenegger, & Fehr, 2011;Eisenegger, Treyer, Fehr, & Knoch, 2008;Knoch, Pascual-Leone, Meyer, Treyer, & Fehr, 2006;Tassy et al, 2012). Talairach coordinates (Talairach & Tournoux, 1988) for the dmPFC were x = 1.5, y = 31.5, and z = 35.5; these coordinates were taken from previous neuroimaging work demonstrating an activation of this region during social impression updating (Mende-Siedlecki et al, 2012).…”
Section: Transcranial Magnetic Stimulation (Tms)mentioning
confidence: 99%
“…Similar stimulation parameters (i.e., fixed intensity of stimulation, 15 minutes of stimulation) have been used before to suppress activity of prefrontal regions prior to task requiring social judgments (e.g., reciprocal fairness, moral judgments), with the effects of stimulation continuing after the end of the actual stimulation (e.g., Baumgartner, Knoch, Hotz, Eisenegger, & Fehr, 2011;Eisenegger, Treyer, Fehr, & Knoch, 2008;Knoch, Pascual-Leone, Meyer, Treyer, & Fehr, 2006;Tassy et al, 2012). Talairach coordinates (Talairach & Tournoux, 1988) for the dmPFC were x = 1.5, y = 31.5, and z = 35.5; these coordinates were taken from previous neuroimaging work demonstrating an activation of this region during social impression updating (Mende-Siedlecki et al, 2012).…”
Section: Transcranial Magnetic Stimulation (Tms)mentioning
confidence: 99%
“…Results of studies of Herrington et al (2005) and Baumgartner et al (2011) (as it is described in section ''Thermodynamics of framing-effect, intuitive and rational decisions'') based on fMRI analysis correlate with the data obtained by Heller (1993), Gimranov and Kurdyukova (2005). From the standpoint of thermodynamics the results received during research of above mentioned authors, once again testify that after impact on closed system (brain) in this case by use of TMS there is fluctuations which as a result lead system to an equilibrium state and the order is created.…”
Section: About ''An Emotion Conservation Law''mentioning
confidence: 54%
“…Naqvi et al (2006) suggest that moral decisions, compared to nonmoral decisions, engage emotions, especially when one is required to consider the consequences of one's actions for another's well-being. Baumgartner et al (2011) have found that when fairness and economic self-interest were in conflict, normal subjects (who make costly normative decisions at a much higher frequency) displayed significantly higher activity in, and connectivity between, the right DLPFC and the posterior ventromedial prefrontal cortex (pVMPFC). In contrast, when there was no conflict between fairness and economic self-interest, both types of subjects displayed identical neural patterns and behaved identically.…”
Section: Thermodynamics Of Framing-effect Intuitive and Rational Decmentioning
confidence: 99%
“…Eight out of 28 contrasts contributed to the cluster in vmPFC (MDE 5 21.26%; 2MDE 5 35.87%) (Table III). Self-gain/other-lost > Self-lost/other-gain 12 Beyer et al [2014a] 40 Self-won/other-lost > Self-lost/other-won 12 Beyer et al [2014b] 41 Self-won/other-lost > Self-lost/other-won 3 Brunnlieb et al [2013] 15 Self-won/other-lost > Self-lost/other-won 25 Cikara et al [2011] 18 Favored team's success/rival team's failure > control 9 Delgado et al [2008] 17 Self-gain/other-lost > Self-lost/other-gain 5 Du et al [2013] 19 Self-won/others-lost > self-lost/others-won 12 Dvash et al [2010] 16 Relative gain > relative loss 6 Emmerling et al [2016] 15 Self-won/other-lost > Self-lost/other-won 9 Fareri and Delgado [2014] 18 Self-won/others-lost > self-lost/others-won: social > non-social 8 Fliessbach et al [2007] 33 Self-won/other-lost > self-lost/other-won 1 self-lost/other-lost 8 Fliessbach et al [2012] 64 Self-won/other-lost > self-lost/other-won 1 self-lost/other-lost 2 Haruno & Frith [2010] 52 Parametric analysis, positive correlation with absoluate differences between two peoeple (self > other) Baumgartner et al [2011] 32 disadvantageous outcomes > equal outcomes 17 Beyer et al [2014a] 40 Self-lost/other-won > Self-won/other-lost 7 Beyer et al [2014b] 41 Self-lost/other-won > Self-won/other-lost 5 Cikara et al [2011] 18 Favored team's failure/rival team's success > control 3 Civai et al [2012] 19 disadvantageous outcomes > equal outcomes 12 Corradi-Dell'Acqua et al [2016] 19 disadvantageous outcomes > equal outcomes 21 Emmerling et al [2016] 15 Self-lost/other-won > Self-won/other-lost 4 Fatfouta et al [2016] 23 disadvantageous outcomes > equal outcomes 18 Farmer et al [2016] 18 disadvantageous outcomes > equal outcomes 6 Feng et al [2016] 40 disadvantageous outcomes > equal outcomes 10 Fliessbach et al [2012] 64 disadvantageous outcomes > equal outcomes 1 Gospic et al [1983] 17 disadvantageous outcomes > equal outcomes 4 Gradin et al [2015] 25 disadvantageous outcomes > equal outcomes 10 Guo et al [2013a] 18 disadvantageous outcomes > equal outcomes 10 Guo et al [2...…”
Section: Primary Ale Meta-analysis Resultsmentioning
confidence: 99%